Analisis Yuridis atas Pelanggaran Bersifat Mendesak sebagai Dasar Pemutusan Hubungan Kerja dalam Perspektif Hukum Ketenagakerjaan - Nashifa Tsarwa; Ahmad Fadhil Ubaidillah; Jeremia Hamonangan Siagian (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The concept of “urgent violation” as regulated in Article 52 paragraph (2) of Government Regulation No. 35 of 2021 introduces a new ground for employment termination (PHK), granting employers the authority to unilaterally terminate workers. However, this provision lacks a clear definition and objective parameters, creating legal uncertainty and potential misuse. This study employs a normative juridical method with a descriptive-analytical approach through literature review of legislation, Constitutional Court decisions, and labor law literature. The findings indicate that the clause on “urgent violation” often emerges from unequal bargaining positions between employers and workers, thereby failing to fully satisfy the principle of consensualism as a requirement for valid agreements. Substantively, this provision resembles the “serious misconduct” norm under Article 158 of the Manpower Law, which was annulled by the Constitutional Court through Decision No. 012/PUU-I/2003 for violating the presumption of innocence and workers’ constitutional rights. Consequently, the regulation on “urgent violation” risks repeating the same legal shortcomings and contradicts the spirit of labor law, which emphasizes that termination of employment must be avoided and only used as a last resort (ultimum remedium), as affirmed in Article 151 of the Manpower Law.